(3QSGdI JaSjQjIs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s ((3GHf GdedG (B"(3GHQGgje Hf GMeO(B" s)
(3ChdgG (B:s
(3bGd GdYGQa HGddg eMeO Hf Ydi GdMGJei GdGfOdSj, GdMeO ddg GdPi NdY Ydi YHGOI Cgd GdYfGjI s
(3BNQgG (B:s
(3agPG ePgH GdMGJeI ef Cgd GdeeKdjf dGeQ Gddg hYdi eKd gPG djS JUfjai s
(3Vef eLehY , JQJjHgG (B: (3GdQGHY YTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs